Penerapan Pembelajaran Sentra Bahan Alam/Sains terhadap Perkembangan Kreativitas Anak Kelompok B di RA Salafiyah Syafi’iyah Klinterejo Sooko Mojokerto - Nurul Farihah (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2018)
This study aims to determine the effect of learning center of natural materials/science on creativity development of groub B children in RA Salafiyah Syafi’iyah Klinterejo Sooko Mojokerto. In this study data obtained in the form of ordinal data and not normally distributed, So statistical analysis used is non-parametic statistic. Non parametic statistical test used is wilcoxon pairs test. Based on data analysis, it is known that the value of Zhitung obtained is 4,24 (price (-) is not taken into account because the price is absolute). The next step, giving interpretation to Zhitung by first looking for Ztabel price by consulting with the level of sigtifikansi equal to 0,025 so that obtained by Ztabel price equal to 1,96. If Zhitung > Ztabel then the null hypothesis is rijected, otherwise if Zhitung < Ztabel then null hypothesis accepted. From the above research it is known that Zhitung > Ztabel (4,24 > 1,96) then null hypothesis (H0) is rejected. This means that the application of learning centers of nature/science has an influence on creativity in children.